ANALISIS USAHATANI DAN KETAHANAN PANGAN RUMAH TANGGA PETANI KUBIS DI KECAMATAN SUMBEREJO KABUPATEN TANGGAMUS - Chairil Ihsan; Rabiatul Adawiyah; Tubagus Hasanuddin (Lampung University, 2021)
This study aims to analyze the farming income, household income, farming constraints, contribution of farming income, household food security level, correlation between household food security level and farming production as well as cabbage farmers’ income. This research has been carried out in the village of Dadapan and Simpang Kanan, Sumberejo Sub District, Tanggamus Regency. This research is a survey involving 56 cabbage farmers selected using simple random sampling. Data were collected in July-August 2019. The research data were analyzed using qualitative descriptive and quantitative methods. The results of this research shows that cabbage farming income is IDR15,643,452.38 per area of 0,36 hectare annually which contributed to 64.54 percent of IDR28,017,440.48 household income per year. Constraints faced by cabbage farmers are the handling of leaf worms, armyworms, leaf spots, club roots, out model equipment, delayed distribution of fertilizer from farmer groups, decreased cabbage price that is fluctuated every season, and lack of attention from extension agencies. Food security status of cabbage farmer households is 50.00 percent in food secure, 26.79 percent in less secure, 14.8 percent in food vulnerable, and 8.93 percent in food insecure. There is a significant correlation between household food security level and farming production as well as cabbage farmers’ income.Key words: cabbage farming, food security, household income